Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1101/225144
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell-free prototyping strategies for enhancing the sustainable production of polyhydroxyalkanoates bioplastics

Abstract: The polyhydroxyalkanoates are a group of microbially-produced biopolymers that have been proposed as sustainable alternatives to several oil-derived plastics. However, polyhydroxyalkanoates are currently more expensive to produce than oil-derived plastics and therefore, more efficient production processes would be desirable. Cell-free transcriptiontranslation-based metabolic engineering strategies have been previously used to optimise several different biosynthetic pathways but not the polyhydroxyalkanoates bi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 71 publications
(43 reference statements)
0
17
0
Order By: Relevance
“…For example, environmental conditions can be varied within a wider range to favor product formation [ 4 ]; transportation issues across cell membranes are eliminated [ 5 ]; toxic compounds can be produced at much higher titers than the cell’s tolerance limit [ 6 ]. Because components of the biosynthetic pathways can be readily mix-and-matched in a combinatorial fashion, cell-free biosynthesis has also been used as a high-throughput prototyping tool to inform pathway design in whole-cell biosynthesis [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, environmental conditions can be varied within a wider range to favor product formation [ 4 ]; transportation issues across cell membranes are eliminated [ 5 ]; toxic compounds can be produced at much higher titers than the cell’s tolerance limit [ 6 ]. Because components of the biosynthetic pathways can be readily mix-and-matched in a combinatorial fashion, cell-free biosynthesis has also been used as a high-throughput prototyping tool to inform pathway design in whole-cell biosynthesis [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biologically based bioplastics to replace those derived from petroleum have been a source of interest for many research groups. Kelwick et al (2018) described an E. coli-based cell-free system for the production of polyhydroalkanoate (PHA) plastics from whey permeate in an enzyme cascade with constitutive phaCAB operon products, β-galactosidase and acetyl-CoA provided by glycolysis and aided by a plasmid carrying T 7 RNA polymerase. The authors note that the biodegradable PHA plastics are more expensive to produce than the petroleumsourced products and suggested that the system proposed would be valuable at the microplate level in the search for more efficient producer combinations (see section "Cell-Free Enzyme Pathways").…”
Section: Cell-free Enzyme Pathwaysmentioning
confidence: 99%
“…These systems can also be an appropriate platform for production because of lower noise and toxicity and absence of resource competition between pathway and cell growth. To date, cell-free systems have been applied to implement pathways for violacein [49], 4-BDO [50], polyhydroxyalkanoates bioplastics [51], mevalonate [52], n-butanol [53] and raspberry ketone [54], using either transcriptiontranslation (TX-TL) systems, overexpressed enzymes in the crude extract or purified enzymes. Advantages and possibilities of cell-free systems for metabolic engineering has been reviewed elsewhere [55], and a methods chapter for pathway prototyping in cell-free systems has recently been published [56].…”
Section: Custom-made Biosensors' New Application Domain: Cell-free Mementioning
confidence: 99%